EFEKTIVITAS COGNITIVE BEHAVIOR THERAPY TERHADAP PENURUNAN INTENSITAS WAKTU PENGGUNAAN GADGET PADA REMAJA - Temo, Fine; Rakinaung, Natalia; Polii, Grace (Fakultas Keperawatan, Universitas Katolik De La Salle Manado, 2023)
Introduction: The use of gadgets is currently in great demand for all groups, especially among adolescents, but the use of gadgets is no longer controlled, causing users to experience dependence on playing gadgets to the point of forgetting their impact on health. Cognitivebehavior therapy is a solution by adolescents to prevent the negative effects of gadget addiction. Objective: This research aimed to determine the effectiveness of cognitive behavior therapyon reducing the intensity of time in using gadgets of adolescents at SMA Negeri 2 Langowan. Method: This was quantitative research using the pre-experimental research design with one group pretest posttest design approach. The researchwas carried out at SMA Negeri 2 Langowan, North Langowan District, Minahasa Regency.The population was all students of class X MIPA1 at SMA Negeri 2 Langowan and the data was collected using the total sampling technique with the sample of n = 26 respondents. The instrument used was an observation sheet on the Intensity of Gadget Usage Time. Results: This research used the Wilcoxon Signed Rank statistical test. Based on the results of data analysis of the intensity of time in using gadgets before and after being given cognitive behavior therapy, the result shows mean rank post-test 10.50 and pre-test 0.00 with significant ρ-value was obtained = 0.000 (ρ= <0.05) whichmeans cognitive behavior therapy is effective to reducing time intensity in using gadget. Conclusions: As the conclutions of this study is cognitive behavior therapy is effective in reducing the intensity of time in using gadgets towards adolescents.